Optically Active Nanostructured ZnO Films. Issue 50 (22nd October 2015) - Duan, Yingying; Han, Lu; Zhang, Jialiang; Asahina, Shunsuke; Huang, Zhehao; Shi, Lin; Wang, Bo; Cao, Yuanyuan; Yao, Yuan; Ma, Liguo; Wang, Cui; Dukor, Rina K.; et al.
Abstract: Inorganic nanomaterials endowed with hierarchical chirality could open new horizons in physical theory and applications because of their fascinating properties. Here, we report chiral ZnO films coated on quartz substrates with a hierarchical nanostructure ranging from atomic to micrometer scale. Three levels of hierarchical chirality exist in the ZnO films: helical ZnO crystalline structures that form primary helically coiled nanoplates, secondary helical stacking of these nanoplates, and tertiary nanoscale circinate aggregates formed by several stacked nanoplates. These films exhibited optical activity (OA) at 380 nm and in the range of 200–800 nm and created circularly polarized luminescence centered at 510 nm and Raman OA at 50–1400 cm −1, which was attributed to electronic transitions, scattering, photoluminescent emission, and Raman scattering in a dissymmetric electric field. The unprecedented strong OA could be attributed to multiple light scattering and absorption‐enhanced light harvesting in the hierarchical structures. Abstract : Chiral inorganic materials : ZnO films (see picture) were deposited on quartz substrates usingL /D ‐methionine as both a structure‐directing and symmetry‐breaking agent. Three levels of hierarchical chirality were studied in the ZnO films. The multiple optical activities of these films were attributed to electronic transitions, photoluminescent emission, and Raman scattering.